An investigation into stylistic devices in ‘the thorn birds’ by colleen mccullough and their vietnamese translational equivalents - Phan,Thị Kim Dung; Lê Tấn Thi (ĐHĐN : ĐHĐN., 2015)
This is a study of stylistic devices in the novel “The Thorn Birds” by Colleen McCullough. The data for analysis in this thesis are the original work and the Vietnamese translational version “tieng chim hot trong bui man gai” translated by Pham Manh Hung. The research is carried out based on the combination of a variety of methods, namely qualitative, quantitative, statistics, descriptive, analytic, synthetic, and induce. The study analysed three stylistic devices: metaphor, metonymy and simile of different subjects. It also investigates into the effective assistance of stylistic devices in literary analysis. On one hand the researcher expects to prove the important role of stylistic devices to literary analysis. On the other, the researcher hopes to find out the semantic features of these stylistic devices and their translational equivalents in the target language by Phạm Mạnh Hùng in the Vietnamese version. On the basis of the findings, this research also suggests some implications for learners and readers. This helps them understand stylistics devices well and apply in their teaching and learning literature. This also helps readers master these linguistic devices in order to become more skillful in interaction of language.
Master thesis in social sciences and humanities
Keywords: stylistic devices in ‘the thorn birds’ by colleen mccullough and their vietnamese translational equivalents; stylistic devices in ‘the thorn birds’ -- vietnamese translational equivalents